High antiphospholipid antibody levels are associated with statin use and may reflect chronic endothelial damage in non-autoimmune thrombosis: cross-sectional study. Issue 6 (3rd March 2012) - Broder, Anna; Tobin, Jonathan N; Putterman, Chaim
Abstract : Objective: Persistently elevated antiphospholipid antibodies and positive lupus anticoagulant (LAC) are associated with an increased risk of thrombosis. The objective of this study was to explore whether antiphospholipid antibody and/or LAC positivity were associated with the traditional risk factors for thrombosis or with medication use in patients without autoimmune diseases hospitalised with arterial or venous thrombosis. Design: Cross-sectional study. Setting: Montefiore Medical Center, a large urban tertiary care centre. Patients: 270 patients (93 with deep vein thrombosis (DVT) or pulmonary embolism (PE), and 177 with non-haemorrhagic stroke (cerebrovascular accident (CVA)) admitted between January 2006 and December 2010 with a discharge diagnosis of either DVT, PE or CVA, who had LAC and antiphospholipid antibodies measured within 6 months from their index admission. Patients with lupus or antiphospholipid syndrome were excluded. Main Outcome Measures: The main dependent variable was antiphospholipid antibodies of 40 units or greater (antiphospholipid antibody positivity) and/or LAC positivity. Independent variables were traditional thrombosis risk factors, statin use, aspirin use and warfarin use. Results: 31 (11%) patients were LAC positive and/or antiphospholipid antibody positive. None of the traditional risk factors at the time of DVT/PE/CVA was associated with antiphospholipid antibody positivity. Current statin use was associated with an OR of 3.2 (95% CI 1.3 to 7.9, p=0.01) of antiphospholipid antibody positivity, adjusted for age, ethnicity and gender. Aspirin or warfarin use was not associated with antiphospholipid antibody levels. Conclusion: If statin therapy reflects the history of previous hyperlipidaemia, high levels of antiphospholipid antibodies may be a marker for earlier endothelial damage caused by hyperlipidaemia.